Spectral overlap of far-red light with chlorophyll fluorescence causes artifacts in PAM-based ΦPSII determination - Park, Ji Up; Zheng, Youbin; Kim, Jongyun (Frontiers in Plant Science, 2026)
Far-red light (FR, 700–800 nm) can enhance photosynthesis by stimulating photosystem I (PSI). However, during chlorophyll fluorescence (CF) measurements using pulse-amplitude modulation (PAM) fluorometry, unusually high quantum yields of photosystem II (ΦPSII) have been observed under high FR light intensities, raising concerns about measurement artifacts. To test this, we constructed light response curves for sweet basil (Ocimum basilicum L.) grown under light-emitting diode (LED) light (R:G:B = 44%:18%:38%) with varying photosynthetic photon flux densities (PPFD, 0–1,000 μmol m−2 s−1) and FR fractions (0, 0.26, 0.45, and 0.63). FR treatments consistently increased ΦPSII, but when total photon flux density (TPFD, 400–800 nm) exceeded 1,000 μmol m−2 s−1, ΦPSII rose abruptly. Nonfluorescent reference tests using white and black paper confirmed that FR induced spurious fluorescence signals, likely due to spectral overlap between FR photons and the PAM detection range (680–760 nm). Tilting the LED panel to reduce reflected FR eliminated the abrupt ΦPSII peak but introduced unexpectedly increased ΦPSII across treatments, likely due to probe-induced shading. These findings demonstrate that high-intensity FR can confound PAM-based CF measurements by producing spurious signals unrelated to plant physiology. Accurate and reliable assessment of photosynthetic performance under extended spectral lighting conditions requires careful management of lighting geometry and FR intensity.